Hyperuricemia and Associated Factors in Children with Chronic Kidney Disease: A Cross-Sectional Study - Jie Xu; Lingxiao Tong; Jianhua Mao (MDPI AG, 2021)
Background: Hyperuricemia is increasingly recognized as a risk factor for chronic kidney disease (CKD) just in adults. The purpose of this study was to investigate the clinical characteristics of hyperuricemia and its associated factors in Chinese children with CKD at a single center. Methods: A cross-sectional study of 170 CKD children collected from the Department of Nephrology, The Zhejiang University Children's Hospital was conducted. The clinical data, including anthropometric data, blood pressure measurements, and biochemical parameters, were recorded and analyzed retrospectively. The factors associated with hyperuricemia in CKD children were evaluated by Pearson and Spearman correlation analysis and multiple logistic regression analysis. Results: The mean age was 9.79 ± 4.10 years, and 72 (42.35%) were girls. Higher blood urea nitrogen (BUN), serum creatinine, cystatin C, D-dimer, lower hemoglobin, albumin, and estimated glomerular filtration rate (eGFR) were significantly associated with higher serum uric acid (SUA). In multiple logistic regression analysis, anemia and higher BUN were both positively associated factors, whereas eGFR ≥ 90 mL/min/1.73 m2 was a negatively associated factor for subjects with SUA ≥ 390 µmol/L (6.5 mg/dL). Conclusions: SUA was significantly associated with kidney risk factors in CKD children. Monitoring and controlling SUA, Hb, BUN, and Scr levels in CKD children may help to prevent the progression of CKD.